The non-divergence Newton-based Load Flow Method in ill conditioned system - Shahriari, A.; Mokhlis, Hazlie; Bakar, A.H.A.; Karimi, M.; Aman, M.M. (International Journal of Scientific & Engineering Research, 2012)
This paper implements the Optimal Multiplier Load Flow Method (OMLFM) in polar coordinate form to calculate low voltage solution and maximum loading point of system in ill conditioned system. OMLFM modifies the direction of state variables (buses voltage and phase) by using optimal multiplier in order to the convergence of load flow equations in ill conditioned system. The privilege of OMLFM emerges in keeping dimension of load flow jacobian matrix constant. While another method such as continuation and homotopy methods change the framework of jacobian matrix based on predictor and corrector steps in term of increasing load demand. Actually, the calculation process of SSSM is based on standard Newton Raphson load flow method. The validation of OMLFM for maximum loading point as ill-conditioned system is shown by testing IEEE 57 bus test system. Furthermore, the 13 bus radial transmission system is tested to with verify OMLFM for ill conditioned system includes high R/X ratio lines and the weak interconnection.